A Mixed Methods Approach to Investigating the Employment Decisions of Aged Care Workers in Australia - Jefferson, Therese; Austen, S.; Sharp, R.; Ong; Adams, V.; Lewin, G. (2016)
This chapter describes the development and implementation of a mixed methods research project that was designed to investigate the characteristics and experience of women aged 45 and over working in the Australian aged care sector. The key issue of interest is whether these workers planned to remain in or leave employment in the sector. This study utilizes an embedded mixed methods framework of enquiry, utilizing secondary data from a large national survey, organizational employment data, purposefully collected survey data, and semi-structured interview data collection and analysis. This framework captures the potential of quantitative data to identify national patterns of mature-age women’s employment, the employment decisions made by aged care workers at an organizational level, and patterns of employment exit and retention by aged care workers at an industry level. Individual qualitative data provide insights into the experiences of the aged care workers within specific institutional contexts.